Improvement of Traffic Movement for Roads Network in Al-Kadhimiya City Center - Mohammed Qadir Ismael, Ass. Prof. Dr.; Ali Jasim Mohammed, MSc student (Journal of Engineering, 2016)
Numerous regions in the city of Baghdad experience the congestion and traffic problems. Due to the religious and economic significance, Al-Kadhimiya city (inside the metropolitan range of Baghdad) was chosen as study area. The data gathering stage was separated into two branches: the questionnaire method which is utilized to estimate the traffic volumes for the chosen roads and field data collection method which included video recording and manual counting for the volumes entering the selected signal intersections. The stage of analysis and evaluation for the seventeen urban roads, one highway, and three intersections was performed by HCS-2000 software.The presented work plots a system for assessing the level of service for roads network within the study region. Moreover, several improvement alternatives were proposed to overcome the traffic movement operations issues. This work shows that traffic facilities currently undergoing serious degradation causing a traffic jam. Therefore, the implementation of some remedial action is necessary to improve the level of service for these facilities.